Effect of follicular development after ovulation synchronization on Premature luteolysis in Awassi sheep. (Damascus University Journal of agriculture sciences, 2023)
The purpose of the present study was to investigate the possibility to alleviate premature luteolysis by replacing the ovulation inducing agent hCG by GnRH. Thirty-nine Awassi ewes were equally and randomly assigned, 72 h after artificial insemination (AI), to one of three treatment groups. Ewes in the first group received 37.5 µg of the GnRH analogue (Lecirelin), the second were injected with 1000 I.U. of  hCG and the third group served as a control and received 1 mL physiological saline solution (Control). Blood samples, collected at daily intervals after the time of GnRH treatment, were analyzed for plasma progesterone, estradiol and, cholesterol concentrations. Ovarian follicles were monitored at the time of GnRH administration, 60 and 84 hours with the aid of a real-time ultrasound scanner equipped with a 7.5 MHz transrectal linear array transducer. Antral follicles were counted and measured with electronic calipers. Pregnancy was diagnosed ultrasonographically at day 32 after AI. All statistical analyses were performed using the SAS package.Numbers, sizes and diameters of ovarian follicles among treatment groups throughout the inspection period did not differ (P>0.05). Onset and duration of estrus were not significantly affected by treatment (P>0.05). No significant differences (P>0.05) were recorded in cholesterol, estradiol and progesterone concentrations among the treatment groups during the inspection period. Premature lutolysis became evident in ewes with longer estrus durations by day 6.25 after AI and amounted to 7.69%, 18.18 % and 23.07% in GnRH, hCG and control group, respectively. The expected reduction in the incidence of luteal insufficiency in GnRH group didn't reach the significance level (P>0.05). This reduction is considered substantial despite its statistical insignificance. Pregnancy rates increased to 92.31% and 81.82% in GnRH and hCG groups, respectively, compared to %76.92 in the control group. From the results it may be concluded that GnRH was more effective in reducing premature luteolysis than hCG. Substitution of hCG for GnRH as ovulation inducing agent was not beneficial.
Keywords: GnRH; hCG; Ovsynch; Luteolysis; Awassi sheep